Percy Jackson and the Greek Heroes - Riordan Rick (Great Britain PENGUIN, 2015)
IF YOU LIKE POISONINGS, BETRAYALS, MUTILATIONS, MURDERS AND FLESH-EATING FARMYARD ANIMALS, KEEP READING . . . In this gripping follow-up to Percy Jackson and the Greek Gods, demigod Percy Jackson tells the stories of twelve of the original Greek heroes in all their gory, bloodthirsty glory. Want to know who cut off Medusa's head? Which hero was raised by a she-bear? Who tamed Pegasus, the winged horse? Percy has all the answers . . .